2005
DOI: 10.1111/j.1369-7625.2005.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

From rhetoric to reality: including patient voices in supportive cancer care planning

Abstract: Objective To explore the extent and manner of patient participation in the planning of regional supportive care networks throughout the province of Ontario. We consider the disconnect between the rhetoric and reality of patient involvement in network planning and co-ordination. ContextIn 1997, the Province of Ontario, Canada, established a new, regionalized cancer care system. By transferring responsibility to the regional level and to networks, the architects of the new provincial system hoped to broaden part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
(96 reference statements)
0
24
0
Order By: Relevance
“…In Ontario, the ''Life to Gain'' cancer policy planning process ''ring-fenced'' one-third of all committee and working group seats for cancer patients, establishing consumers as full participants in the process. From 2002 onwards, the same province initiated a patient involvement strategy in the development of new, regional supportive care networks; however, an evaluation concluded that the ''attempt'' had ''failed'', finding a significant gap between intentions to involve patients in health planning and their actual involvement (Gold et al, 2005). User involvement also appears in Australia, with organisations such as Cancer Voices New South Wales facilitating involvement in service planning (Cancer Voices NSW, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…In Ontario, the ''Life to Gain'' cancer policy planning process ''ring-fenced'' one-third of all committee and working group seats for cancer patients, establishing consumers as full participants in the process. From 2002 onwards, the same province initiated a patient involvement strategy in the development of new, regional supportive care networks; however, an evaluation concluded that the ''attempt'' had ''failed'', finding a significant gap between intentions to involve patients in health planning and their actual involvement (Gold et al, 2005). User involvement also appears in Australia, with organisations such as Cancer Voices New South Wales facilitating involvement in service planning (Cancer Voices NSW, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…A third factor possibly limiting patient involvement may be a lack of guidance. Interviews with health professionals in Canada revealed that patients were not involved in planning for regional supportive care networks as intended because there were no directions provided on how to achieve this [8].…”
Section: Hypothesized Barriers To Patient Involvement In Service Evalmentioning
confidence: 96%
“…Studies examining the nature of patient participation in service planning have found that most activities are limited to various forms of consultation, rather than interactive partnerships as are advocated for treatment decision-making [8,9]. Patient involvement in service evaluation has largely been restricted to completing satisfaction surveys [10].…”
Section: Patient Involvement In Health Carementioning
confidence: 99%
“…[7][8][9][10][11][12][13][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] See Figure 1 for details.…”
Section: Synthesismentioning
confidence: 99%
“…40 Another report which looked at the planning of regional supportive cancer services in Ontario, Canada, focused generally on barriers to effective patient involvement. 41 The final case study reference was a web link to 24 reports produced between 2005 and 2012 by the Scottish Health Council on behalf of the Scottish Government. 42 As with the English NHS, Scottish Health Boards are required to involve patients and local communities adequately in relation to significant NHS service change.…”
Section: Case Studiesmentioning
confidence: 99%